ダイ44ジ ナンキョク チイキ カンソクタイ ナツタイ 「センヨウ カンソクセン」 コウドウ ホウコク 2003 - 小達, 恒夫; オダテ, ツネオ; Odate, Tsuneo (2004)
P(論文) 第44次日本南極地域観測隊(JARE-44)では,南極地域観測第期5か年計画のプロジェクト研究観測を実施するため,2回目となる海洋観測のための「専用観測船」による航海を行った.JARE-44ではJARE-43の観測結果を踏まえ,生物生産過程の違いがもたらす温暖化関連ガス成分の生成除去過程や有機物の鉛直輸送過程に焦点を絞ったプロセス研究を行うこととした.本航海前には東京水産大学「海鷹丸」の観測(平成15年1月2月)が,本航海後にはJARE-44「しらせ」の観測(平成15年3月)が行われ,一連の観測により同一海域の時系列観測となった.「専用観測船」として,JARE-43と同じ,「タンガロア号」(ニュージーランド水圏大気研究所)が傭船された.2月17日,ニュージーランドウェリントン港を出航後,連続航走観測を行いながら,東経140-145度,南緯61度以南の観測海域を目指した.2月25日から3月6日の期間に,集中的な観測を行った.停船観測の終了後,ウェリントン港へ向けて航走し,3月12日にはウェリントン港外へ到達した. The second cruise for marine science was conducted as one of the projects under the five year plan Phase VI of the Japanese Antarctic Research Expeditions (JARE-43 to -47). The Research Vessel Tangaroa (National Institute of Water and Atmospheric Research, New Zealand) was chartered for the cruise. This cruise was one of the time-serial observations shared by the TS Umitaka Maru (Tokyo University of Fisheries, Japan) in January-February 2003 and icebreaker Shirase (JARE-44) in March. Our cruise focused on process studies to reveal the relationship between plankton community variations, and biogenic green house gas production/removal and vertical transport of organic matter. The RV Tangaroa departed from Wellington, New Zealand, on the 17th of February 2003. She cruised to the study area (140-145°E , 61-65°S ), while conducting continuous observations. Station observations started on 25th February (local time) and finished on 6th March. After the station observations, continuous surface water observations were conducted again between the study area and Wellington. RV Tangaroa returned to the ocean just outside the port of Wellington on 12th March. departmental bulletin paper